Kepentingan Rusia Mengirimkan Bantuan Militer Ke Libyan National Army Pada Perang Sipil Libya Ke-2 - Nasution, Salsabila Aulia Putri; Suwecawangsa, Adi Putra; Nugraha, A.A Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
Russia's involvement in the Second Libyan Civil War can be seen from the military aid sent to the Libyan National. Russia's decision was taken despite the risk of violating an arm embargo imposed by the UN Security Council under Security Resolution 1970. This research which uses the qualitative descriptive method to observe Russia's interest in the military aid sent, also uses Neorealism, Offensive Realism and National Interest perspectives. This research hence presents an explanation of which there is a threat to Russia's economy from the relations between Turkey and the Governmental of National Accord in the dynamic of The Second Libyan Civil War. The perceived threat then forces Russia to support Libyan National Army. Furthermore, this research also shows that there are Russia's economic interests to make Libya the center of business in the Energy sector due to its abundant potential and strategic location. at last, Russia's interest is to become a new super power in the MENA region due to the minimum intervention from the West